Rhetorical Bodies and Movement-Images in the 1949 Tamil Film Velaikari (House Maid). Issue 1 (February 2018) - Ravindran, Gopalan
Abstract : The notion of 'rhetorical bodies' argues the cause of the rhetorical elements in the material and the material elements in the rhetorical in ways that can be seen as analogous to the bi-partite modes of Deleuzian film philosophy, 'movement-image' and 'time-image'. Tamil films of the 1940s and 1950s bear the strong imprints of the rhetorical elements of the Self-Respect Movement and Dravidian Movement, which took root in different versions during the 1920s–60s. The narrative locations of the bodies (both male and female) in the Tamil films of the 1940s and 1950s provide interesting theoretical and analytical challenges if one seeks to combine the Deleuzian notions of 'movement-image' with the notions of material rhetorics. The coming together of these notions provides new pointers to the understanding of an important phase in the history of Tamil cinema for its implications on the long-running nexus between politics and films in the state of Tamil Nadu. The Deleuzian trajectory in film philosophy provides more than enough pointers to examine early Tamil cinema's attempts to construct 'movement-images' through rhetorical bodies. This paper seeks to examine the contexts of 'movement-images' and the role of 'rhetorical bodies' in constructing the same in Velaikari (1949), scripted by C. N. Annadurai. Popularly known as Aringnar Anna, C. N. Annadurai was the former Chief Minister of Tamil Nadu and the Founder of DMK ( Dravida Munnetra Kazhakam ), the party which unseated Congress from power in Tamil Nadu in 1967, and the state remains out of reach of the national parties ever since.